Development of a scalable recombinant system for cyclic beta-1,2-glucans production - Guidolin, Leticia Soledad (2024)
Background Cyclic β-1,2-glucans (CβG) are bacterial cyclic homopolysaccharides with interesting biotechnologicalapplications. These ring-shaped molecules have a hydrophilic surface that confers high solubility and a hydrophobiccavity able to include poorly soluble molecules. Several studies demonstrate that CβG and many derivatives canbe applied in drug solubilization and stabilization, enantiomer separation, catalysis, synthesis of nanomaterials andeven as immunomodulators, suggesting these molecules have great potential for their industrial and commercialexploitation. Nowadays, there is no method to produce CβG by chemical synthesis and bacteria that synthesize themare slow-growing or even pathogenic, which makes the scaling up of the process difficult and expensive. Therefore,scalable production and purification methods are needed to afford the demand and expand the repertoire ofapplications of CβG.Results We present the production of CβG in specially designed E. coli strains by means of the deletion of intrinsicpolysaccharide biosynthetic genes and the heterologous expression of enzymes involved in CβG synthesis, transportand succinilation. These strains produce different types of CβG: unsubstituted CβG, anionic CβG and CβG of high size.Unsubstituted CβG with a degree of polymerization of 17 to 24 glucoses were produced and secreted to the culturemedium by one of the strains. Through high cell density culture (HCDC) of that strain we were able to produce 4,5 gof pure unsubstituted CβG /L in culture medium within 48 h culture.Conclusions We have developed a new recombinant bacterial system for the synthesis of cyclic β-1,2-glucans,expanding the use of bacteria as a platform for the production of new polysaccharides with biotechnologicalapplications. This new approach allowed us to produce CβG in E. coli with high yields and the highest volumetricproductivity reported to date. We expect this new highly scalable system facilitates CβG availability for furtherresearch and the widespread use of these promising molecules across many application fields.